2015
DOI: 10.1111/jfpp.12585
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Various Processing Techniques on Dissipation Behavior of Antibiotic Residues in Poultry Meat

Abstract: Instant research was planned to study the dissipation behavior of antibiotic residues in chicken meat using various heat‐processing treatments. Purposely, poultry birds were procured and administered with antibiotics for a period of 42 days. Chicken meat, after slaughtering, was processed through boiling, grilling, microwaving and roasting techniques to assess the impact of processing on antibiotic (enrofloxacin, ciprofloxacin, oxytetracycline and doxycycline) residues through high‐performance liquid chromatog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 20 publications
(30 reference statements)
1
6
1
Order By: Relevance
“…Whereas our results were in differs with those results declared by Khan et al, (2016) who found that ciprofloxacin residues in chicken tissues could be degraded by roasting processes by 68.76%. From the point of view these results were in accordance with those reported by Khan et al, (2016) who deduced that microwaving can degrade ciprofloxacin residues. Our current results were disagreed with those achieved by Javadi (2011) who revealed that highly detectable residual amount of enrofloxacin residues in chicken tissues were appeared after microwaving.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Whereas our results were in differs with those results declared by Khan et al, (2016) who found that ciprofloxacin residues in chicken tissues could be degraded by roasting processes by 68.76%. From the point of view these results were in accordance with those reported by Khan et al, (2016) who deduced that microwaving can degrade ciprofloxacin residues. Our current results were disagreed with those achieved by Javadi (2011) who revealed that highly detectable residual amount of enrofloxacin residues in chicken tissues were appeared after microwaving.…”
Section: Discussioncontrasting
confidence: 99%
“…These results were differed with those achieved by Khan et al (2016) that they found that ciprofloxacin residues in chicken tissues were degrade by boiling by 68.18 %.These results were agreed with those obtained by Lolo et al (2006) who decided that enrofloxacin residues in chicken tissues didn't degrade by grilling .The current results were disagreed with those obtained by Fathy et al (2015) who decided that ciprofloxacin amounts in chicken tissues could be degraded by grilling from 5999.3ppb to 1956.61ppb.In the same lines the present results were in un acceptance with those reported by Khan et al, (2016) who found that ciprofloxacin residues in chicken tissues degrade after grilling by 33.34%.The achieved results were agreed with those obtained by Lolo et al, (2006) who decided that enrofloxacin residues didn't degrade by roasting. Whereas our results were in differs with those results declared by Khan et al, (2016) who found that ciprofloxacin residues in chicken tissues could be degraded by roasting processes by 68.76%. From the point of view these results were in accordance with those reported by Khan et al, (2016) who deduced that microwaving can degrade ciprofloxacin residues.…”
Section: Discussionsupporting
confidence: 63%
“…Although these two antibiotics were considered to have a lower risk and are most commonly used on chicken farms worldwide [20,21,24], frequent and regular use can accelerate the resistance process [5,25]. Previous studies have reported high rates of resistance to amoxicillin and oxytetracycline in poultry in China and other countries [11,26,27]. This eventually leads farmers to use higher level of medically important antibiotics or other antibiotics on the prohibited list [28,29].…”
Section: Famers' Practice Of Antibiotic Usementioning
confidence: 99%
“…Moreover, OTC residue not detected after boiling of liver from rabbit after 3 Weeks of its injection by OTC (Morshdy et al 2014). Lower result reported by Khan et al (2015) who reported that OTC residue level in broiler liver reduction percent by grilling is 33%, by roasting is 55%, by boiling is 62% and by microwaving is 64%.…”
Section: Resultsmentioning
confidence: 58%